2010
DOI: 10.1242/jcs.067538
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a small vasohibin-binding protein (SVBP) and its role in vasohibin secretion

Abstract: SummaryUpon stimulation with angiogenic factors, vascular endothelial cells (ECs) secrete a negative-feedback regulator of angiogenesis, vasohibin-1 (VASH1). Because VASH1 lacks a classical signal sequence, it is not clear how ECs secrete VASH1. We isolated a small vasohibin-binding protein (SVBP) composed of 66 amino acids. The level of Svbp mRNA was relatively high in the bone marrow, spleen and testes of mice. In cultured ECs, Vash1 mRNA was induced by VEGF, and Svbp mRNA was expressed constitutively. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 48 publications
3
62
0
1
Order By: Relevance
“…Here, we showed that CM from human VASH2 transfectants stimulated the migration of endothelial cells. Ovarian cancer cells express SVBP, a secretory chaperone of vasohibins (15). These results suggest that VASH2 is secreted from the cancer cells and acts on neighboring endothelial cells to stimulate angiogenesis in a paracrine manner.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Here, we showed that CM from human VASH2 transfectants stimulated the migration of endothelial cells. Ovarian cancer cells express SVBP, a secretory chaperone of vasohibins (15). These results suggest that VASH2 is secreted from the cancer cells and acts on neighboring endothelial cells to stimulate angiogenesis in a paracrine manner.…”
Section: Discussionmentioning
confidence: 83%
“…The amino acid sequence of the human VASH2 protein is 52.5% homologous to that of human VASH1, and both VASH1 and VASH2 are highly conserved among species. VASH1 and VASH2 lack the classical signal sequence; but they bind to the small intracellular vasohibin-binding protein (SVBP), and this binding with SVBP facilitates their secretion (15). Because of the similarity between VASH1 and VASH2, we examined their expression and function by the use of hypoxia-induced subcutaneous angiogenesis in mice.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the critical role of VASH-1 in the maintenance of endothelial cells against cellular stressors and the regulatory mechanisms of its synthesis via posttranscriptional regulation mediated by the binding of HuR proteins to AU-rich elements in the 3′ untranslated region of VASH-1 mRNAs have been reported [9]. VASH-1 does not contain a classic signal sequence; rather, a small vasohibin-binding protein (SVBP) serves as its secretory chaperon and contributes to its antiangiogenic effects [10]. To date, no cell surface receptors for VASH-1 have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, VASH-1 inhibits lymphangiogenesis and lymph node metastasis of tumors (16). VASH-1 does not contain a classic signal sequence, and a small vasohibin-binding protein (SVBP) serves as a secretory chaperon for VASH-1 and contributes to the antiangiogenic effects of VASH-1 (39). To date, cell surface receptors for VASH-1 have not been reported.…”
mentioning
confidence: 99%